Acute effects of muscle stretching on physical performance, range of motion, and injury incidence in healthy active individuals: a systematic review - Behm, D. G.; Blazevich, A. J.; Kay, A. D.; McHugh, M. (Applied Physiology, Nutrition, and Metabolism, 2016)
Recently, there has been a shift from static stretching (SS) or proprioceptive neuromuscular facilitation (PNF) stretch ing within a warm-up to a greater emphasis on dynamic stretching (DS). The objective of this review was to compare the effects of SS, DS, and PNF on performance, range of motion (ROM), and injury prevention. The data indicated that SS- (-3.7%), DS- (+1.3%), and PNF- (-4.4%) induced performance changes were small to moderate with testing performed immediately after stretching, possibly because of reduced muscle activation after SS and PNF. A dose-response relationship illustrated greater performance deficits with =60 s (-4.6%) than with <60 s (-1.1%) SS per muscle group. Conversely, SS demonstrated a moderate (2.2%) perfor mance benefit at longer muscle lengths. Testing was performed on average 3-5 min after stretching, and most studies did not include poststretching dynamic activities; when these activities were included, no clear performance effect was observed. DS produced small-to-moderate performance improvements when completed within minutes of physical activity. SS and PNF stretching had no clear effect on all-cause or overuse injuries; no data are available for DS. All forms of training induced ROM improvements, typically lasting <30 min. Changes may result from acute reductions in muscle and tendon stiffness or from neural adaptations causing an improved stretch tolerance. Considering the small-to-moderate changes immediately after stretching and the study limita tions, stretching within a warm-up that includes additional poststretching dynamic activity is recommended for reducing muscle injuries and increasing joint ROM with inconsequential effects on subsequent athletic performance